1993
DOI: 10.1002/pola.1993.080310722
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase‐catalyzed synthesis of lignin–phenol copolymers

Abstract: SYNOPSISHorseradish peroxidase catalyzes the copolymerization of phenols with kraft lignin in aqueous-organic solvent mixtures. Nearly all of the lignin and over one-third of the phenol (either p-cresol or p-phenylphenol) is incorporated into the copolymer which is highly insoluble in dimethylformamide (DMF) , presumably because of crosslinking of lignin molecules via polyphenol bridges. The copolymer consists of 80% lignin, by weight. In the absence of a phenol, lignin is polymerized into a noncrosslinked, DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…Thus, copolymerization of lignin with cresol lowers the endothermic glass transition temperature. This is consistent with published reports performed in non-aqueous media (Blinkovsky and Dordick, (1993). Therefore, the incorporation of phenol into lignin does not appear to destroy the native structure of the lignin; albeit bound phenols can radically alter its thermal properties.…”
Section: Thermal Propertiessupporting
confidence: 82%
See 2 more Smart Citations
“…Thus, copolymerization of lignin with cresol lowers the endothermic glass transition temperature. This is consistent with published reports performed in non-aqueous media (Blinkovsky and Dordick, (1993). Therefore, the incorporation of phenol into lignin does not appear to destroy the native structure of the lignin; albeit bound phenols can radically alter its thermal properties.…”
Section: Thermal Propertiessupporting
confidence: 82%
“…Hence, significant differences between the lignin-cresol copolymer and free lignin are most likely due to the distributions of incorporation of cresol into lignin or/and polycresol segments in the copolymer. Blinkovsky et al (1993) observed that the FTIR spectrum of lignin-cresol is strongly different from that of polycresol obtained in aqueous-organic solvent mixtures, but not in reversed micelles. …”
Section: Rate Of Copolymerizationmentioning
confidence: 93%
See 1 more Smart Citation
“…While the crystal structure of HRP has not been determined, the active-site structure is believed to be similar to cytochrome C peroxidase, with the Arg-183 residue in HRP corresponding to Ser-185 in cytochrome C peroxidase [30][31][32]. This enzyme is catalytically active in organic media [33][34][35], has a wide specificity with substrates (phenols) that are highly soluble in organic solvents, is commercially available in the pure protein form, and has a structural 'marker' (i.e. active-site heme group) to aid in the elucidation of solvent-induced structural perturbations in the active site.…”
Section: Synthesis Of a New Family Of Polyphenols By Enzymatic Oxidatmentioning
confidence: 99%
“…Blinkovsky and Dordick [35] have reported the HRP-catalyzed copolymerization of phenols with kraft lignin in aqueous-organic solvent mixtures. Besides cellulose and hemicellulose, lignin is the most abundant polymer on earth.…”
Section: Mechanism Of Polymerizationmentioning
confidence: 99%